Hacia la renovación de concepciones y prácticas de la planeación y el desarrollo (2010)
ABSTRACT: The hereinafter reflection focuses its attention in the analysis of the execution of the experience called Local Planning and Participative Budget Program (PPPP) implemented during the 2004-2007 period in the “Comuna 1” of the municipality of Medellín-Colombia, identifying strengths and tensions that assessed it, to a some extent, as a typical case of planning for the territory development (Gutiérrez y Sánchez, 2009). In such sense, planning is understood as a social intervention process that belongs to social sciences, since it defines and guides generating intentions of activated participation by people aiming at the improvement of their wellbeing and life conditions. Development, understood as the historically and territorially determined multiple socio-cultural construction (Múnera, 2007); and planning as the social, political, territorial and strategic process (Gutiérrez and Sánchez, 2009); were considered as the guiding conceptual references. The hereinbefore conceptual points of view concur through four binding matters: the individual, sociopolitical, chronological and strategic aspects, which together as a group, constitute planning for the territory development; these matters allow the theoretical-practical relation on which the conceptions and practices renewal proposal is supported from the (PPPP) analytical description.